Lending conditions in EU: The role of credit demand and supply - Svatopluk Kapounek; Zuzana Kučerová; Jarko Fidrmuc (Leibniz-Institut für Ost- und Südosteuropaforschung (IOS), 2017)
We analyse the bank lending activity after the financial crisis and focus on bank-specific supply factors. Using a rich microeconomic dataset from Bankscope and macroeconomic shocks data, we employ OLS and 2SLS fixed effects models with banking controls, macroeconomic shocks and institutional quality. The banks' loan-rate spreads increased despite the recent policy of low interest rates and quantitative easing. We use the bank asset quality as instruments to capture exogenous changes in loan supply. The empirical evidence shows that loan-rate spread and through this the supply of loans is negatively affected by a low asset quality and capital ratios.
urn:nbn:de:101:1-201703141156
Keywords: E58; G21; G28; 330; bank lending; loans; financial vulnerability; loan-rate spreads; institutions; macroeconomic shocks